2002
DOI: 10.1128/jcm.40.12.4700-4704.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Pathogenetic Basis for Shedding and Transmission of Ovine Gamma Herpesvirus 2

Abstract: Ovine herpesvirus 2 (OvHV-2), a member of the viral subfamily Gammaherpesvirinae, shares numerous similarities with human herpesvirus 8 (HHV-8). Both viruses are apathogenic in their healthy original host, may cause lymphoprolipherative diseases, cannot routinely be propagated in cell culture, and may be sexually transmitted. However, the pathways of sexual transmission of these viruses, as well as the underlying pathogenetic dynamics, are not well understood. Organs from naturally OvHV-2-infected, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 16 publications
1
33
1
9
Order By: Relevance
“…Gammaherpesviruses do not typically establish latency in nasal tissues, but are shed from this site during active infection (Hussy et al, 2002). The detection of PhaHV-1 and -2 only in the nasal tissue of …”
mentioning
confidence: 99%
“…Gammaherpesviruses do not typically establish latency in nasal tissues, but are shed from this site during active infection (Hussy et al, 2002). The detection of PhaHV-1 and -2 only in the nasal tissue of …”
mentioning
confidence: 99%
“…Though we did not attempt other transmission routes in this study, there have been several reports that no OvHV-2 DNA was detected in the urinary bladder [2], urine or faeces [7,8]. Consequently, it is suggested that nasal secretions play an active role in transmission of the virus among sheep.…”
Section: Discussionmentioning
confidence: 99%
“…OvHV-2 collected from ovine nasal secretions can infect naive sheep, cattle or bison [79,80]. OvHV-2 viral DNA also has been detected in samples from the alimentary, respiratory and uro-genital tracts of sheep [35] indicating that some infection of offspring may occur during or shortly after lambing or calving. However, other studies have documented spread of OvHV-2 from sheep to bison over distances of up to 5 km [49].…”
Section: Transmission and Incidencementioning
confidence: 99%
“…The causative agent, OvHV-2 is transmitted by contact or aerosol, mainly from less than a year old lambs [40]. A strong association between OvHV-2 outbreaks in different susceptible animals and exposure to sheep has been documented in the literature [5,35,54]. The respiratory tract is a common route for both entry and shedding of many herpesviruses in animals.…”
Section: Transmission and Incidencementioning
confidence: 99%